An Evaluation of the Successes and Shortcomings in Change Management of a Language Institution in Colombia - Palmer, Varlene (2018)
This study attempts to bridge the gap between English language learning and teacher management and development. In comparison to the numerous research papers written about Asian and European language teaching organisations, this research focuses on a less researched path, Latin America. It evaluates the successes and shortcomings in change management of a language institution in Colombia, through the analysis of management and leadership in language teaching organisations, staff motivation, teacher development and management of change. The case study aims to answer the questions: (1) What were the attitudes of the teachers, concerning how the change affected them? (2) How do the change management methods of the DOS compare to the change management methods of the literature? (3) Why was the change successful or unsuccessful? The findings have suggested that the change and change management were a success.